2017
DOI: 10.29312/remexca.v0i15.425
|View full text |Cite
|
Sign up to set email alerts
|

Potencial económico y agronómico de la adopción de semillas de maíz genéticamente modificado en México

Abstract: ResumenA partir de la evidencia generada en la adopción de soya genéticamente modificada, realizamos un análisis a través de paneles de productores en cinco sistemas de producción de maíz de riego y temporal en México, con el propósito de determinar el potencial económico y agronómico de adopción de semillas de maíz genéticamente modificada en la producción. Los resultados muestran que el potencial económico y agronómico de adopción del maíz genéticamente modificado es "medio" en los sistemas de producción de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The maize that is imported in Mexico comes from the USA [7], so authors such as [24,25] maintain that the aversion of the Mexican population toward transgenic maize is unjustified, since the deficit between production and consumption is actually covered with transgenic maize. In this regard, [4] found that the cultivation of native races in Mexico contributes to imports of the grain being lower and ensures food security of the regions with greatest social backwardness, where, in addition, the native races show higher resilience to the rainfed environmental conditions, which has allowed them to remain in the preference of subsistence producers [26,27].…”
Section: Grain Maize Production and Consumption At The Global Levelmentioning
confidence: 99%
See 3 more Smart Citations
“…The maize that is imported in Mexico comes from the USA [7], so authors such as [24,25] maintain that the aversion of the Mexican population toward transgenic maize is unjustified, since the deficit between production and consumption is actually covered with transgenic maize. In this regard, [4] found that the cultivation of native races in Mexico contributes to imports of the grain being lower and ensures food security of the regions with greatest social backwardness, where, in addition, the native races show higher resilience to the rainfed environmental conditions, which has allowed them to remain in the preference of subsistence producers [26,27].…”
Section: Grain Maize Production and Consumption At The Global Levelmentioning
confidence: 99%
“…However, when using the decomposition of production growth factors model proposed by [14], the apparent efficiency in the production system did not consider that the growth of grain maize productivity between six-year periods presented a decreasing trend, since it went from 16.4% in 1995-2000 compared to 1989-1994, to 6.9% in 2013-2018 compared to 2007-2012 (Table 5). According to [8,25] the growth from 1983 to 2000 is explained by the strengthening of the policies for centralized support in agricultural production, technological research, guarantee prices, use of improved varieties and fertilizers, supports for commercialization, credit, and agricultural insurance. The decrease in productivity since 2001 coincides with a stage of policies for decentralized support to the farmland, where the private sector participated in technological changes, research, dissemination, and promotion of input use; and where producers made their own decisions about the destination of the subsidies contributed by the government [25].…”
Section: Grain Maize Productivity In Mexicomentioning
confidence: 99%
See 2 more Smart Citations